2017
DOI: 10.1080/14789949.2017.1337801
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of pharmacological treatment with prisoners experiencing high levels of hypersexual disorder

Abstract: This paper presents an evaluation of the impact of pharmacological treatment in reducing hypersexual disorder in adult males who have been incarcerated following conviction for a sexual offence. The evaluation compares two types of pharmacological treatment, one of which is part of the current NICE guidance for treatment of hypersexuality (Antiandrogens), whilst the other type (SSRIs) is off-label use in the UK for hypersexuality. The participant pool comprised 127 adult male prisoners serving sentences for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Outcomes indicated that 17 patients experienced a significant reduction of CSB symptoms with naltrexone pharmacotherapy. Winder et al (2017) evaluated and compared two types of pharmacological treatment for HD (antiandrogens and SSRIs) among incarcerated male sex offenders. The results indicated that both SSRIs and antiandrogens significantly reduce hypersexual behavior and sexual preoccupation.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Outcomes indicated that 17 patients experienced a significant reduction of CSB symptoms with naltrexone pharmacotherapy. Winder et al (2017) evaluated and compared two types of pharmacological treatment for HD (antiandrogens and SSRIs) among incarcerated male sex offenders. The results indicated that both SSRIs and antiandrogens significantly reduce hypersexual behavior and sexual preoccupation.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…More recently, research using a pre‐post‐design, carried out in the United Kingdom with incarcerated sex offenders, showed that both SSRIs and testosterone‐lowering drugs significantly reduced sexual preoccupation, strength of sexual fantasies, and compulsions, as well as improving general well‐being (Winder et al, 2014; Winder et al, ). Other medication studies agree (Lewis, Grubin, Ross, & Das, ; Thibaut et al, ).…”
Section: Pharmacological Interventions For Sex Offendersmentioning
confidence: 99%
“…In the past decade, there have been three published articles on the use of SSRIs to treat sex offenders with sexual preoccupation and/or so‐called “hypersexuality.” In a sample of 51 men treated with SSRIs, there was a reduction in “hypersexuality, sexual preoccupation, and sexual compulsivity.” However, the participants in this study were also treated with anti‐androgens (Winder et al, ). When comparing the effectiveness of an anti‐androgen (cyproterone acetate) with two SSRIs (fluoxetine or paroxetine), it was found that all three medications were effective in reducing sexual preoccupation and “hypersexuality” after 1 month of use (Winder et al, ). Patients reported that the SSRIs helped them to address inappropriate fantasies and helped improve “self‐regulation.” However, an adverse side‐effect of being on SSRIs reported in this study was difficulty achieving and/or maintaining an erection.…”
Section: Treatment Studiesmentioning
confidence: 99%
“…Generally, research on pharmacological treatments consists of using gonadotropin-releasing hormone (GnRH) agonists, anti-androgens (such as cyproterone acetate or medroxyprogesterone acetate), and selective serotonin reuptake inhibitors (SSRIs) (Khan et al, 2015). These drugs are used internationally (Turner, Petermann, Harrison, Krueger, & Briken, 2017) and are effective in reducing sexual preoccupation and sex drive (Winder et al, 2018). It is important to remember that it is unethical to coerce a person who has committed a sex offense to receive surgical or pharmacological treatments and that revocable, informed consent must be obtained before beginning treatment (Rice & Harris, 2011;Shaw, 2019).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation